Prognostic impact of moderate or severe mitral regurgitation (MR) irrespective of concomitant comorbidities: a retrospective matched cohort study. Issue 7 (17th July 2014) - Prakash, Roshan; Horsfall, Matthew; Markwick, Andrew; Pumar, Marsus; Lee, Leong; Sinhal, Ajay; Joseph, Majo X; Chew, Derek P
Abstract : Objective: We sought to objectively quantify the independent impact of significant mitral regurgitation (MR) on prognosis in patients with multiple comorbidities and ascertain the extent to which median survival is affected by increasing comorbidities. Methods: This was a retrospective matched cohort study using a clinical-echocardiography reporting database linked to a clinical and administrative database in an Australian tertiary hospital. We identified our study cohort (patients with significant MR) and control cohort (without MR) on transthoracic echocardiographies performed between 2005 and 2010. The main outcome measures were mortality and heart failure rehospitalisation. A Cox proportional hazards model was used to adjust for clinical covariates and the 'win ratio' methodology was utilised to estimate the impact of MR on main outcomes. Results: A total of 218 matched patients with and without significant MR were followed-up for 1 year. Significant MR was associated with an adjusted HR for mortality of 1.83 (95% CI 1.28 to 2.62, p<0.001). The win ratio for death and death or heart failure readmission was 0.57 (95% CI 0.40 to 0.78, p=0.0002) and 0.53 (95% CI 0.39 to 0.71, p<0.0001), respectively. Significant MR with left ventricular (LV) systolic dysfunction and age between 75 and 85 years were associated with a substantial reduction in median survival by 2.3 years. Significant MR with LV systolic dysfunction, age beyond 85 and advance comorbidities were associated with a lesser reduction in median survival by 0.2 years. Conclusions: Significant MR in patients with multiple comorbidities leads to increase in death and heart failure rehospitalisation with reduced estimated median survival. However, its impact diminishes with increasing comorbidities.